Molino Metro Central an integrated transport hub and civic center - Gargantos, Gideone Cyrus F.; Meonada, Jose Mari (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
In this age of rapid development in the Philippines, the need for transport infrastructure is at an all-time high, especially for the cities at the fringes of Metro Manila. However, excessive focus towards infrastructure often results in a disconnect between the built environment of the infrastructure and its users. With this year's undergraduate thesis theme of "North and south : architecture that aids to unite a developing nation in the forefront of inclusivity, community building and growth," the Molino Metro Central is anchored on the currently ongoing Metro Manila Subway Project in order to maximize the potential of the development while also introducing a new form of public transportation to existing ones. As such, the Molino Metro Central aims to create an architecture that transcends to typical transport hub archetype into a place that focuses on the experience of each user and its context to the rest of the communities in Molino, Bacoor. With the careful integration of socio-civic spaces into a collective transport interchange, the Molino Metro Central create a dynamic that encourages interaction and community revitalization, without sacrificing the efficiency and empowerment of its users through their transport experience.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Transport infrastructure -- Design -- Philippines